2022
DOI: 10.3390/ijms232012570
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing and In Silico Analysis of Human Sertoli in Patients with Non-Obstructive Azoospermia

Abstract: Non-obstructive azoospermia (NOA) is a serious cause of male infertility. The Sertoli cell responds to androgens and takes on roles supporting spermatogenesis, which may cause infertility. This work aims to enhance the genetic diagnosis of NOA via the discovery of new and hub genes implicated in human NOA and to better assess the odds of successful sperm extraction according to the individual’s genotype. Whole exome sequencing (WES) was done on three NOA patients to find key genes involved in NOA. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…A high quality and relevance of gene prioritization can be seen in this network, which contains five of the eight canonical markers. As well as finding novel regulators of SSC self-renewal, we suggest the refined network could be used to identify target genes for male infertility and testicular cancer treatment [16,29,[31][32][33]. DOI: http://dx.doi.org/10.5772/intechopen.112964…”
Section: Spermatogonia Stem Cell Gene Ontology and Signaling Pathway ...mentioning
confidence: 99%
“…A high quality and relevance of gene prioritization can be seen in this network, which contains five of the eight canonical markers. As well as finding novel regulators of SSC self-renewal, we suggest the refined network could be used to identify target genes for male infertility and testicular cancer treatment [16,29,[31][32][33]. DOI: http://dx.doi.org/10.5772/intechopen.112964…”
Section: Spermatogonia Stem Cell Gene Ontology and Signaling Pathway ...mentioning
confidence: 99%
“…The field of male reproduction would benefit from technologies that would identify rare sperm for patients with NOA. There is a challenge in stimulating sperm production in patients with NOA through medical or regenerative approaches ( 8 - 11 ). The cystic fibrosis transmembrane conductance regulator ( CFTR ) gene, known for its role in the pathogenesis of cystic fibrosis, has been implicated in the etiology of azoospermia, particularly congenital bilateral absence of the vas deferens (CBAVD).…”
Section: Priorities For Future Researchmentioning
confidence: 99%
“…More importantly, silencing the expression of circ_MGLL results in an increase in the proliferation of Sertoli cells ( 19 ). However, many studies have reported that changes in the population or function of Sertoli cells are among the main factors leading to defective spermatogenesis ( 20 ). Nevertheless, the clinical relevance of circ_MGLL in patients with iNOA remains to be determined.…”
Section: Introductionmentioning
confidence: 99%